T Transformasi Peran KOPPONTREN dalam Membangun Kemandirian Ekonomi Pesantren: Analisis Model Bisnis dan Tata Kelola Berkelanjutan - Zain Zain; Aunur Rofiq; Segaf Segaf (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
Islamic boarding schools (pesantren) in Indonesia face economic independence challenges due to reliance on traditional donative funding. The urgency of this study lies in the limited holistic research on Islamic Boarding School Cooperatives (KOPONTREN) as a strategic solution to address this gap and strengthen community-based sharia economy. This research aims to analyze the institutional transformation of KOPONTREN as a hybrid institution in building pesantren economic independence through a descriptive qualitative approach with thematic content analysis of 41 relevant academic references (2000–2025) on pesantren economy, sharia cooperatives, and Islamic governance. The findings indicate that KOPONTREN evolves as an adaptive response to modernization, functioning as a hybrid institution integrating Islamic values, modern management practices, business model innovation (agribusiness, education, social finance), and sustainable governance principles. This study contributes a conceptual synthesis model with four pillars, affirming KOPONTREN as a driver of people’s economy and a strategic instrument for long-term pesantren resilience.